2002
DOI: 10.1073/pnas.132252399
|View full text |Cite
|
Sign up to set email alerts
|

Isolated allogeneic bone marrow-derived mesenchymal cells engraft and stimulate growth in children with osteogenesis imperfecta: Implications for cell therapy of bone

Abstract: Treatment with isolated allogeneic mesenchymal cells has the potential to enhance the therapeutic effects of conventional bone marrow transplantation in patients with genetic disorders affecting mesenchymal tissues, including bone, cartilage, and muscle. To demonstrate the feasibility of mesenchymal cell therapy and to gain insight into the transplant biology of these cells, we used gene-marked, donor marrow-derived mesenchymal cells to treat six children who had undergone standard bone marrow transplantation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
1,063
3
31

Year Published

2003
2003
2012
2012

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 1,519 publications
(1,123 citation statements)
references
References 37 publications
(31 reference statements)
11
1,063
3
31
Order By: Relevance
“…Notably, the i.v. infusion of allogeneic MSC in humans has led to encouraging results in different human diseases including GVHD [15], breast cancer [71], osteogenesis imperfecta [72], metachromatic leukodystrophy and Hurler syndrome [73], hematological malignancies [74] and stroke [75]. However, recent in vivo experiments raised some doubts about the reported immunoprivilege of MSC, indicating that at least in some cases, administration of allogeneic MSC into an MHC-mismatched host may result in their rejection [19].…”
Section: Msc-mediated Immunological Effects In Vivomentioning
confidence: 99%
“…Notably, the i.v. infusion of allogeneic MSC in humans has led to encouraging results in different human diseases including GVHD [15], breast cancer [71], osteogenesis imperfecta [72], metachromatic leukodystrophy and Hurler syndrome [73], hematological malignancies [74] and stroke [75]. However, recent in vivo experiments raised some doubts about the reported immunoprivilege of MSC, indicating that at least in some cases, administration of allogeneic MSC into an MHC-mismatched host may result in their rejection [19].…”
Section: Msc-mediated Immunological Effects In Vivomentioning
confidence: 99%
“…En effet, l'observation qu'une population multiclonale donne plusieurs lignages peut s'expliquer par la coexistence de populations unipotentes, chacune pour un des quatre lignages. Il est ainsi attendu que les CSM puissent régénérer l'os et le cartilage lésés, ce qui a été largement démontré dans de nombreux modèles précliniques, dont celui de l'ostéogenèse imparfaite [20] [28]. Selon ce modèle, explicité en premier lieu pour les cellules souches hématopoïétiques (CSH), les cellules souches expriment, avant toute induction de différenciation vers leurs différents lignages, certains gènes caractéristiques de ces lignages, dont certains facteurs-clés de transcription.…”
Section: La Multipotenceunclassified
“…En effet, l'observation qu'une population multiclonale donne plusieurs lignages peut s'expliquer par la coexistence de populations unipotentes, chacune pour un des quatre lignages. Il est ainsi attendu que les CSM puissent régénérer l'os et le cartilage lésés, ce qui a été largement démontré dans de nombreux modèles précliniques, dont celui de l'ostéogenèse imparfaite [20], et par quelques essais cliniques [40] (➜). Il est aussi attendu que les CSM puissent participer à la reconstruction de la vasculature, ce qui a été démontré dans quelques études récentes in vitro et in vivo [21,41] …”
Section: La Multipotenceunclassified
“…The authors concluded that bone marrow transplantation from normal donors to OI patients might be of benefit in OI. [44][45][46] The number of donor cells that engrafted in marrow recipients was however very small. At 3 months after bone marrow transplantation, only 1.5-2% of the cells in trabecular bone of the cell recipients were estimated to be of the donor origin.…”
Section: Analysis Of the Ceramic Cubes At Different Time Pointsmentioning
confidence: 99%
“…Previous studies in mice and humans have demonstrated that bone marrow-derived mesenchymal stem cells will migrate to bone when administered systemically. [37][38][39]46 We previously showed that direct injection of the cells into the mouse bone marrow cavity leads to a wide distribution of the cells in different tissues of the host. 39 Since early treatment for OI will be essential, mesenchymal stem cells transduced with therapeutic genes will need to be delivered early during development.…”
Section: Ex Vivo Gene Delivery To Bonementioning
confidence: 99%